Critical Ethics
XI, 284 p.
Keywords: The current resurgence of ethics in the beleaguered humanities reflects an increasing anxiety about the value and utility of critical/philosophical debate in the wake of poststructuralism. This book addresses this 'return to ethics' in relation to a wide variety of theories and texts. It covers substantial areas of ethical debate, particularly in relation to queer politics, biography, history, postmodernism, atrocity literature, utilitarianism, pedagogy and the philosophy of science. Theorists discussed in the volume include Rorty, Heidegger, Levinas, Mill, Lyotard, Leavis, Kuhn, Davidson, Nussbaum and Freud.